Robinsoniella peoriensis, originally isolated from swine manure, and early periprosthetic hip infection: Case report and review of the literature. (December 2016) - Rieber, Heime; Frontzek, Andre; Bell, Andreas; Frommelt, Lars
Abstract: We report on the first case of a periprosthetic joint infection with the anaerobic spore-forming Gram-positive rod Robinsoniella peoriensis as the causative agent. The bacterium was first isolated from a swine manure storage pit and has so far rarely been associated with human infections. Highlights: This is the first case of a periprosthetic joint infection (PJI) caused by Robinsoniella peoriensis. Robinsoniella peoriensis is an anaerobic spore-forming Gram-positive rod. The organism was first isolated from a swine manure storage pit. Microbiologists should be aware that livestock-associated organisms are not necessarily included in medical databases. The patient was successfully treated with a high dose of ampicillin-sulbactam.